Accessibility for people with disabilities in housing area - Abu Bakar, Aniza; Muhamad, Nurliza (2009)
Housing development would normally be considered as mix-development due to the variedness of its development components such as houses, commercial buildings (business area), institutions such as schools and mosque, as well as open space for recreation. People tend to spend most of their time within this territoriality and for the people with disabilities, when the accessibility infrastructure is limited, this would mean spending almost their entire life within the housing unit only. Thus, a study on accessibility for people with disabilities within housing development area is deemed crucial to help them to be more independent and provide optimum opportunity for them to socialize with the society towards a better living environment and better life quality. This paper discusses on the accessibility of people with disabilities with focus on the external environment of the housing neighborhood that linked one component to others such as the housing area itself, the commercial area, schools, mosque and the open space by taking Taman Paroi Jaya, Seremban, Negeri Sembilan as the case study.